An evaluation of the emergence of drug resistant virus for HIV/AIDS drug treatments - Chang, Hyuk-Jun (2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2015)
HIV/AIDS drug treatment, such as highly active anti-retroviral therapy (HAART), often fails due to the emergence of drug resistant species. In this paper we investigate a new estimation method for the possibility of emergence of drug resistant mutation. To the best knowledge of the author this work is the first study to try to describe quantitatively the possibility of drug resistance emergence for HIV/AIDS drug treatments. In simulation studies we compare HIV/AIDS treatment methods, such as structured treatment interruption (STI) and improved gradual dosage reduction (iGDR), based on the proposed analysis. From the analysis we can explain why STI treatment often fails and also can show that iGDR is desirable rather than STI particularly in terms of the decrease of the possibility of emergence of drug resistant virus.